Work Motivation Can Moderates The Influence Of Human Resource Information System On Employee Peformance - Febriyan Muliany; Umi Narimawati; M. Yani Syafei (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research is a quantitative study with an explanatory approach, namely an approach that relies on a number of previous studies as a spring to water the arguments built so that they look fertile and sparkling compared to previous studies. The data used in this study are primary data that researchers obtained from 300 KFC employees spread throughout Indonesia. The data used in this article were analyzed using the smart PLS 4.0 analysis tool. The result in this article show the assumptions accompanied by strong arguments and presented in the Research Hypothesis are concluded to have a positive relationship direction and a significant influence on Employee Performance. This is because the P-Values ​​are positive and below the significance level of 0.05, namely 0.015. These results are because the Human Resource Information System can make employee work easier, can increase work creativity, and can increase work productivity.. In line with the results above, in the next hypothesis, namely the Work Motivation variable can strengthen the influence of the Human Resource Information System variable on Employee Performance because the P-Values ​​are below the significance level of 0.05, namely 0.000, which is more significant than the direct tester 0..015. Thus the data is concluded, the first and second hypotheses in the article can be accepted.